Representasi Ideologi Feminisme Dalam Lirik Lagu Taylor Swift pada Album “Folklore’’ - Triani, Andini I Mayang; Febrian, Febrian (Jurnal Humaniora dan Ilmu Pendidikan, 2025)
Purpose: This study examines feminist ideologies in the lyrics of Taylor Swift's album, Folklore. Research methodology: Using a qualitative descriptive approach and content analysis, the study analyzes three songs—Mad Woman, The Last Great American Dynasty, and Invisible String. The analysis involved identifying phrases depicting women, categorizing them by feminist type, interpreting their meanings, and drawing conclusions. Results: The results of the analysis show that "Mad Woman" critiques gender stereotypes and the effects of gaslighting on women, reflecting resistance to oppressive patriarchal structures. The song "The Last Great American Dynasty" presents a narrative of women who are intended to be the cause of destruction but instead represent the courage to fight against social norms that limit women's freedom. Meanwhile, "Invisible String" offers a more personal perspective, highlighting emotional relationships through the lens of feminism, which values equality and respect in relationships. Conclusion: This study shows that three songs in Taylor Swift's Folklore album represent feminist ideology through critiques of the patriarchy and portrayals of women's empowerment. These findings open up opportunities for further research in the context of popular music consumption. Limitations: This study had several limitations that should be considered. First, the focus of the analysis is only on three songs in Taylor Swift's Folklore album, namely, Mad Woman, The Last Great American Dynasty, and Invisible String. Contribution: This study applies Bhasin and Khan's feminist theory to reveal how feminist messages are conveyed through symbols and narratives in popular music.